Optimal Compatibility in Systems Markets - Sang-Hyun Kim; Jay Pil Choi (Center for Economic Studies and ifo Institute (CESifo), 2014)
We investigate private and social incentives for standardization to ensure market-wide system compatibility in a two-dimensional spatial competition model. We develop a new methodology to analyze competition on a torus and show that there is a fundamental conflict of interest between consumers and producers over the standardization decision. Consumers prefer standardization with full compatibility because it offers more variety that confers a better match with their ideal specifications. However, firms are likely to choose the minimal compatibility to maximize product differentiation and soften competition. This is in sharp contrast to the previous literature that shows the alignment of private and social incentives for compatibility.
Keywords: D43; L13; L22; 330; compatibility; system competition; standardization; spatial competition model; free entry